Robots, Androids and Animatrons: 12 Incredible Projects You Can Build - Lovine John (American : McGraw Hill, 2002)
There’s never been a better time to explore the world of the nearly human. With the complete directions supplied by popular electronics author John Iovine, you can
• Build your first walking, talking, sensing, thinking robot
• Create 12 working robotic projects, using the fully illustrated instructions provided
• Get the best available introduction to robotics, motion control, sensors, and neural intelligence
• Put together basic modules to build sophisticated ‘bots of your own design
• Construct a robotic arm that responds to your spoken commands
• Build a realistic, functional robotic hand
• Apply sensors to detect bumps, walls, inclines , and roads
• Give your robot expertise and neural intelligence
You geteverything you need to create 12 exciting robotic projects using off-the-shelf products and workshop-built devices, including a complete parts list. Also ideal for anyone interested in electronic and motion control, this cult classic gives you the building blocks you need to go practically anywhere in robotics.
Keywords: Kỹ nghệ điều khiển tự động